Characterization of ionophore–doped graphene–based biocomposite thin film for detection of potassium ion using surface plasmon resonance - Zainudin, Afiq Azri (2017)
The preparation of ionophore doped graphene based biocompositeusing chitosan, graphene oxide and valinomycin has been studied. After the reaction, valinomycin immobilized in chitosan–graphene oxide thin film was prepared using spin coating technique. The obtained thin film was characterized and confirmed by Fourier Transform Infrared Spectroscopy (FTIR) and X-Ray Photoelectron Spectroscopy (XPS). Surface morphology was evaluated by atomic force microscopy (AFM), shows the thin film is smooth and homogenous. Absorption and transmittance of the thin film were evaluatedby the ultraviolet-visible (UV-Vis-NIR) spectroscopy. Valinomycin immobilized in chitosan–graphene oxide thin film has been studied as a sensor element for potassium ion by using surface plasmon resonance (SPR). The K+can be detected by measuring SPR signal with a thin film C–GO–V deposited on a gold film when the film in contact with the ion in solution. The sensor produces a linear response for K+up to 100 ppm with a sensitivity 0.00948º ppm-1. These results indicate that the C–GO–V films shows potential for the detection K+in solution.